What is Historicity? - Klausen, Søren Harnow (Res Cogitans, 2020)
ABSTRACT: The article argues for a distinction between standard “historical thinking”, which aims at interpreting theories, views and concepts by considering them in their historical or cultural context, and a more sophisticated “thinking of historicity”, which attempts to uncover the historical nature of human understanding in general. The latter kind of thinking is exemplified, in different ways, by Husserl, Heidegger and Gadamer, who all strongly opposed the trend to “historicize” ideas and knowledge. It is pointed out that the notion of historicity resembles the notion of path-dependence, which has gained prominence in contemporary philosophy of science. It is further argued that precisely because historicity turns out to be a generic and fundamental phenomenon, a part of the human condition, it does not by itself allow one to discriminate between more or less authentic or genuinely historical styles or genres of thinking or research.